Management of diabetes mellitus type-2 in the geriatric population: Current perspectives - Sukhminder Jit Singh Bajwa; Vishal Sehgal; Sanjay Kalra; Manash Pratim Baruah (Wolters Kluwer Medknow Publications, 2014)
The prevalence of diabetes mellitus (DM) has increased exponentially throughout the world and there is rapid increase in elderly diabetics. DM is associated with increased mortality and considerable morbidity including stroke, heart disease, and diminished quality of life in the elderly. However, the unique features of geriatric diabetes have not been given due a prominence in medical literature. Hypoglycemia remains the biggest complicating factor and needs to be avoided in the elderly. Most people in the geriatric age group have some degree of renal insufficiency and medications need to be adjusted wisely with changing renal profile. Because safer and more effective pharmacological therapy is available, an individual approach to DM in the elderly is essential.